A System study of the Balara Filtration Plant - Andres, Garret Raem R.; Garibay, Lemuel; Hilario, Frederick; Rais, Asim. (Diliman, Quezon City College of Engineering, 1992)
The subject of this project study is the Balara Filtration Plant. Although an extensive and thorough study cannot be expected altogether, the group aimed to produce a modest and sincere study consolidated with the genuine desire to learn. Difficulties were encountered because of insufficient data on plant organization and management, production facilities and production system in general. Moreover, the members of the group have to bear out the consequences of the absence of much-needed information like the history of the plant, worker's background, and other information without which a thorough study would be impossible. With these constraints encountered by the group, the project study was successfully accomplished through a series of plant visits. Most of the data were obtained through observations and personal interview with the plant engineers and workers.
Keywords: Balara Filtration Plant; Introduction to industrial Engineering -- IE 3.